1995
DOI: 10.1111/j.1365-3083.1995.tb03712.x
|View full text |Cite
|
Sign up to set email alerts
|

Tenidap, but not Nonsteroidal Anti‐Inflammatory Drugs, Inhibits T‐Cell Proliferation and Cytokine Induction

Abstract: T-lymphocytes are involved in the inflammatory response that occurs in affected joints of patients with rheumatoid arthritis (RA). Some second-line disease modifying anti-rheumatic drugs used in the treatment of patients with RA are known to block T-cell activation. The present study assessed whether tenidap, an investigational anti-rheumatic drug, affects in vitro T-cell responses such as proliferation and cytokine production. It was found that tenidap, in contrast to several nonsteroidal anti-inflammatory dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…It is suggested that prevention of arthritis by CsA and lobenzarit may be due to suppression of key cytokines (IFN-7, TNF and IL-2) during the early stages of disease development [6]. The ability of tenidap to inhibit these T cell cytokines in vivo is consistent with recent reports showing that tenidap inhibits T cell proliferation and cytokine production in vitro [21]. However, complete disease prevention was only noted when tenidap was administered with the adjuvant in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is suggested that prevention of arthritis by CsA and lobenzarit may be due to suppression of key cytokines (IFN-7, TNF and IL-2) during the early stages of disease development [6]. The ability of tenidap to inhibit these T cell cytokines in vivo is consistent with recent reports showing that tenidap inhibits T cell proliferation and cytokine production in vitro [21]. However, complete disease prevention was only noted when tenidap was administered with the adjuvant in this study.…”
Section: Discussionsupporting
confidence: 89%
“…These drugs appear to be effective by suppressing release of interferon-~/(IFN-~'), interleukin-2 (IL-2) and possibly tumour necrosis factor (TNF) from lymph node cells during the initiation of the disease. Recent reports have shown that a new antirheumatic drug, tenidap, also regulates the production of these cytokines in vitro [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that both FLU and MEL inhibited lymphocyte proliferation in a dose-dependent manner in vitro. In humans, COX-2-specific inhibitors such as NS398 (3.1-31 μg/ml) or celecoxib (3.8-38 μg/ml) severely diminished T-cell activation, including IL-2, TNF-α and IFN-γ production, and cell proliferation [9], while the nonselective NSAID tenidap inhibited the production and mRNA expression of IL-2 and IFN-γ in T lymphocytes [7].…”
mentioning
confidence: 99%
“…In humans, some COX‐2 selective NSAIDs inhibited the production of IFN‐γ and TNF‐α, while nonselective NSAIDs inhibited production of IFN‐γ, but not interleukins expression (Dolhain et al. , 1995; Iñiguez et al.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, some COX-2 selective NSAIDs inhibited the production of IFN-c and TNF-a, while nonselective NSAIDs inhibited production of IFN-c, but not interleukins expression (Dolhain et al, 1995;Iñ iguez et al, 1999). In a study about calves, the authors found that FM and some NSAIDs inhibited lymphocytes proliferation in a dose-dependent manner in vitro and tended to decrease the expression of IFN-c, but not interleukins (Maeda et al, 2005).…”
Section: Discussionmentioning
confidence: 99%